Proposed reforms to Singapore Goods and Services Taxation in the digital economy - LIU, Hern Kuan (Institutional Knowledge at Singapore Management University, 2019)
With the rapid development of the digital economy and the increasing importance of GST as a source of tax revenue, the Singapore Government has proposed several reforms to tighten the collection of tax revenue and tap its tax base more efficiently. The reforms focus on activating the currently dormant “reverse charge” mechanism to collect GST on supplies of services “imported” by businesses; creating an “overseas vendor registration regime” to catch digital products “imported” by individuals; and clarifying the “place of supply” requirement for supplies of digital products. This article considers the reforms from the perspective of a foreign business that may potentially be affected and explores the potential implications that are projected to kick in by January 2020. In the upshot, this article argues that the reforms will help the revenue authorities avoid gaps in the Singapore GST regime and better utilise GST as a revenue-collection tool for Singapore.